2019
DOI: 10.1016/j.neubiorev.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Motion adaptation and attention: A critical review and meta-analysis

Abstract: The motion aftereffect (MAE) provides a behavioural probe into the mechanisms underlying motion perception, and has been used to study the effects of attention on motion processing. Visual attention can enhance detection and discrimination of selected visual signals. However, the relationship between attention and motion processing remains contentious: not all studies find that attention increases MAEs. Our meta-analysis reveals several factors that explain superficially discrepant findings. Across studies (37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 83 publications
1
4
0
1
Order By: Relevance
“…This interpretation agrees with past work showing that changing visual attention can influence the amount of adaptation a given stimulus produces (e.g. [17,18]). Whether attention can affect adaptation, and by how much, remains a topic of some debate [18,19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This interpretation agrees with past work showing that changing visual attention can influence the amount of adaptation a given stimulus produces (e.g. [17,18]). Whether attention can affect adaptation, and by how much, remains a topic of some debate [18,19].…”
Section: Discussionsupporting
confidence: 92%
“…[17,18]). Whether attention can affect adaptation, and by how much, remains a topic of some debate [18,19]. Both sides of this debate assume a similar "standard" model of how attention and adaptation interact: Attention strengthens certain neural responses to the attended stimuli in early visual cortex, and these larger responses in turn produce greater amounts of adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…The media was packed in the form of CD and it could be copied directly in computers as well. The initial product development result of this product contained: 1) Eye catcher or attention drawer (Bartlett, Graf, Hedger, &Adams, 2019) in the form of blend of text, font, color, slide show and opening music (Miller, Miller, Turne, &Evans, 2017). 2) Main Menu, in the form usage instructions, material submenu, profile, and, references.…”
Section: Product Developmentmentioning
confidence: 99%
“…Chaudhuri, 1990;Rezec, Krekelberg, & Dobkins, 2004) and against (e.g. Morgan, 2012;Morgan, 2013) a critical role for the attentional mechanisms (for a meta-analysis on motion adaptation and attention see Bartlett, Graf, Hedger, & Adams, 2019). Similarly, studies on adaptation to size showed that the presentation of a demanding central task during adaptation did not affect its magnitude (Tonelli, Pooresmaeili, & Arrighi, 2020) while explicitly moving attention in the direction of the adaptor stimulus was found to even enhance the aftereffect (Kreutzer, Fink, & Weidner, 2015).…”
Section: Introductionmentioning
confidence: 99%